The relationships between neuroglial alterations and neuronal changes in Alzheimer's disease, and the related controversies I: Gliopathogenesis and glioprotection. (14th September 2022) - Toledano-Díaz, Adolfo; Álvarez, M Isabel; Toledano, Adolfo
Since Alois Alzheimer described the pathology of Alzheimer's disease in 1907, an increasing number of studies have attempted to discover its causes and possible ways to treat it. For decades, research has focused on neuronal degeneration and the disruption to the neural circuits that occurs during disease progression, undervaluing in some extent the alterations to glial cells even though these alterations were described in the very first studies of this disease. In recent years, it has been recognized that different families of neuroglia are not merely support cells for neurons but rather key and active elements in the physiology and pathology of the nervous system. Alterations to different types of neuroglia (especially astroglia and microglia but also mature oligodendroglia and oligodendroglial progenitors) have been identified in the initial neuropathological changes that lead to dementia, suggesting that they may represent therapeutic targets to prevent neurodegeneration. In this review, based on our own studies and on the relevant scientific literature, we argue that a careful and in-depth study of glial cells will be fundamental to understanding the origin and progression of Alzheimer's disease. In addition, we analyze the main issues regarding the neuroprotective and neurotoxic role of neuroglial changes, reactions and/or involutions in both humans with Alzheimer's disease and in experimental models of this condition.